2005
DOI: 10.1093/humrep/deh843
|View full text |Cite
|
Sign up to set email alerts
|

Levothyroxine treatment in thyroid peroxidase antibody-positive women undergoing assisted reproduction technologies: a prospective study

Abstract: The pregnancy rate is not affected either by presence of TPOAb or treatment with LT4. However, TPOAb (+) women show a poorer delivery rate compared to TPOAb (-). LT4 treatment in TPOAb (+) does not affect the delivery rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
173
5
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(198 citation statements)
references
References 31 publications
7
173
5
13
Order By: Relevance
“…We initially proposed that patients with anti-thyroid antibodies would be more likely to experience a significant change in TSH because they are naturally predisposed to develop hypothyroidism [9]. This is an important consideration given the negative impact of thyroid antibodies on pregnancy outcomes [5,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…We initially proposed that patients with anti-thyroid antibodies would be more likely to experience a significant change in TSH because they are naturally predisposed to develop hypothyroidism [9]. This is an important consideration given the negative impact of thyroid antibodies on pregnancy outcomes [5,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The studies differed in various aspects. Some had followed a cohort (235)(236)(237)248,250,252,253,(260)(261)(262)(263)(264)(265)(266)(267)(268)(269)(270)(271) (B,A,B,B,B,B,B,A,B-B) and others were "case-controlled" studies (251,254,(272)(273)(274)(275) (C,C,C,C,C).…”
Section: What Is the Role Of Thyroid Autoimmunity In Fertility And Prmentioning
confidence: 99%
“…In contrast, TAbs may be merely reflective of a more general immune diathesis in the women. Although early studies found that levothyroxine (LT 4 ) treatment did not prevent miscarriage in women with TAbs after in vitro fertilization, 16 the same investigators recently reported successful prevention of pregnancy loss in euthyroid women using this approach. 17 If confirmed, these data suggest that it may be appropriate to start treatment with LT 4 at the time of pregnancy in order to reduce the risk of miscarriage and prematurity in euthyroid women with TAbs and suggest that a thyroid diathesis is responsible.…”
Section: Journal Of Women's Healthmentioning
confidence: 99%
“…17 If confirmed, these data suggest that it may be appropriate to start treatment with LT 4 at the time of pregnancy in order to reduce the risk of miscarriage and prematurity in euthyroid women with TAbs and suggest that a thyroid diathesis is responsible. 16 …”
Section: Journal Of Women's Healthmentioning
confidence: 99%